ANALISIS KARAKTER TOKOH DALAM NOVEL AKU MENCINTAINYA MAMA KARYA FREDY S - Asti Riana Sari; Linggua Sanjaya Usop; Lazarus Lonarto; Nanda Welisa Peronika; Raihan Fauzi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
This study aims to describe the characters in the novel Aku Cintanya Mama by Fredy S. The characters in question are (1) the character of the protagonist, (2) the character of the antagonist, and (3) the character of the tritagonist. The research approach used in this study is a qualitative descriptive analysis approach. The source of the data in this study was the text of the Novel Aku Cintanya Mama by Fredy S Published by Bintang Indonesia, in Jakarta 1999, the novel totaled 128 pages. The form of the data in this study is in the form of qualitative data, namely, quotations of words, and sentences that indicate the existence of types of characters in the Novel Aku Cintanya Mama by Fredy S. The data collection technique used in this research is the reading and note technique. The data analysis technique uses a qualitative descriptive method. Based on the research results, Rian's character is kind, friendly, brave and full of love. Tias's character is cruel and spiteful. The character of Rian's father is a mediator, confident, advisory and calm. The character of Rian's mother is caring and worried. Seno's father's character is mediocre and serious. The character of Seno's mother is a mediator. The character of Tias's mother is sensitive, understands, believes and does not have the heart. Seno's character is submissive and advice. Andri's character is advice and obedience. Rudi's character is obedient.